Motivational interviewing and vaccine acceptance in children: The MOTIVE study. Issue 12 (15th March 2022) - Cole, Justin W.; M.H. Chen, Aleda; McGuire, Kalista; Berman, Sarah; Gardner, Julia; Teegala, Yamini
Abstract: Background and Objective: Vaccine coverage have been less than desired in young children in part due to parental vaccine hesitancy. Addressing health beliefs through patient-centered communication approaches such as motivational interviewing (MI) may improve vaccine confidence. Thus, the objective of this study was to determine the difference in paediatric vaccination coverage rates based on the Advisory Committee on Immunization Practices (ACIP) and Centers for Disease Control and Prevention (CDC) recommended schedule in children 0–6 years of age after an educational intervention for providers and integration of an MI-based communication tool, MOTIVE (MO tivational Interviewing T ool to I mprove V accine AcceptancE ). Methods: Paediatric and family practice providers in a federally qualified health center in the United States completed an educational intervention regarding vaccine hesitancy and use of the MOTIVE tool. Providers then implemented the MOTIVE tool to address common health beliefs using strong, presumptive vaccine recommendations and an MI framework during encounters with patients 0–6 years of age. Data were collected from 1-year pre-educational intervention (July 2018-June 2019, N = 2504) and post-intervention (July 2019-March 2020, N = 1954) to examine differences in vaccination coverage rates and documented vaccine refusals. Results: Use of the MOTIVE tool was associated with a statistically significant increase in IIV vaccination coverage rate in children 6 months to 6 years of age (32.4% versus 43.9%, p < 0.01). A significantly increased Hib vaccination coverage rate was observed in children 0–18 months of age. Patients with commercial insurance also had significantly higher vaccination coverage rates for the DTaP, IPV, and VAR vaccines during the intervention period. Use of the MOTIVE tool was associated with a decrease in documented vaccine refusals per 100 patients in children 0–6 years of age (31.5 versus 17.6, p < 0.01). Conclusion: Use of an MI-based communication tool may decrease vaccine refusals and improve childhood vaccination coverage rates, particularly for IIV. Clinical Trial Registration : ClinicalTrials.gov, NCT03934008, https://clinicaltrials.gov/ct2/show/NCT03934008, deidentified individual participant data will not be made available.